Uterine fibroid - new possibilities of nosotropic therapy - A L Tikhomirov (IP Berlin A.V., 2013)
In this article are given the results of studies SMRP: ulipristal acetate in the treatment of uterine fibroids, ulipristal acetate (Esmya).